Landfill gas avoidance projects as an alternative solution in the urban solid waste management - Costa Jordao, Ticiano (Univerzita Pardubice, 2007)
This contribution refers to the potential environmental impacts caused by municipal solid waste landfills due mainly to the release of methane gas. It proposes alternative uses for the landfill gas taking into consideration the current opportunities for investments on landfill gas projects through the Kyoto Protocol and its Clean Development Mechanism. Benefits for the local economy resulting from landfill gas avoidance projects are also highlighted.

This contribution refers to the potential environmental impacts caused by municipal solid waste landfills due mainly to the release of methane gas. It proposes alternative uses for the landfill gas taking into consideration the current opportunities for investments on landfill gas projects through the Kyoto Protocol and its Clean Development Mechanism. Benefits for the local economy resulting from landfill gas avoidance projects are also highlighted.
Keywords: nakládání s odpady; skládky; metan; Kjótský protokol; tuhý komunální odpad; Mechanismus čistého rozvoje